Keberadaan Rumah Negara terhadap Efisiensi Pelaksanaan Tugas dan Motivasi Kerja Pegawai di Rumah Tahanan Negara (Rutan) Kelas IIB Balige Sumatera Utara - Ginting, Syntha Ekanintha; Saleha, Eha (Universitas Terbuka, 2024)
State house is one form of compensation in the form of facilities provided to officials or civil servants as a place of residence in supporting the performance of their duties. residential place in supporting the implementation of their duties. In conducting security in the detention house, it is 24-hour security is required. Employees are required to always be ready to attend office, assist and overcome disturbances to security and order. The existence of this state house is expected to be one of the solutions to support security and disturbances in detention. security and disturbances in detention centers. However, it is necessary to know the extent to which the existence of a state house provides benefits in supporting the efficient implementation of tasks and increase employee motivation. The purpose of this research is to see the effect of the relationship between the existence of a state house on the efficiency implementation of tasks and work motivation at the Balige Class IIB State Detention Center North Sumatra. The method used in this research is quantitative quantitative research method. Data collection techniques are observation and questionnaires. The results of this study indicate that there is a relationship between the existence of a state house and the efficiency of task implementation. with the efficiency of task implementation is significant in the same direction with a moderate relationship, while the relationship with employee motivation is moderate. moderate relationship, while the relationship with employee work motivation is unidirectional with a strong relationship. In conclusion, the existence of a state house can significantly can significantly support the efficiency of task implementation and increase motivation of employees at the Balige Class IIB State Detention Center.